Inadvertent inferior oblique extirpation during orbital decompression. Issue 4 (July 2019) - Karimi, Nasser; Kashkouli, Mohsen Bahmani; Sanjari, Mostafa Soltan; Sianati, Hamed; Sharepour, Maria; Ali, Hadi
Purpose: To report a case of inadvertent inferior oblique extirpation during orbital decompression, its management, and postoperative result. Methods: A 38-year-old female with thyroid eye disease underwent cosmetic right orbital decompression during whichinferior oblique extirpation was noticed. Result: The muscle was repaired on the same session (illustrated in the article) with no postoperative diplopia at 3-month follow-up. Conclusion: Inferior oblique injury should be considered among the uncommon yet important complications of orbital decompression. It can be easily found and repaired in the same session as demonstrated in this case report.